2007
DOI: 10.1590/s0066-782x2007001500002
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do betacaroteno e do tabagismo sobre a remodelação cardíaca pós-infarto do miocárdio

Abstract: After myocardial infarction, smoking and beta-carotene intensified the heart remodeling process; harmful effects of the remodeling process were heightened when the two treatments were used in conjunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…Rafacho et al also showed that after two months of ETS there was a decrease in the cardiac activity of antioxidant enzymes and an increase in LH [ 5 ]. Notably, supplementation with pentoxifylline, retinoic acid and beta-carotene, substances with antioxidant properties, have been shown to attenuate the ventricular remodeling process induced by smoking [ 37 40 ]. However, despite all the evidence showing the major role of ETS in cardiac oxidative damage, no study, until now, has analyzed the participation of lipid peroxidation, protein oxidation and DNA damage as targets of oxidative stress induced by exposure to cigarette smoke in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Rafacho et al also showed that after two months of ETS there was a decrease in the cardiac activity of antioxidant enzymes and an increase in LH [ 5 ]. Notably, supplementation with pentoxifylline, retinoic acid and beta-carotene, substances with antioxidant properties, have been shown to attenuate the ventricular remodeling process induced by smoking [ 37 40 ]. However, despite all the evidence showing the major role of ETS in cardiac oxidative damage, no study, until now, has analyzed the participation of lipid peroxidation, protein oxidation and DNA damage as targets of oxidative stress induced by exposure to cigarette smoke in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of normal rats or rats after infarction to cigarette smoke resulted in the intensifi cation of remodeling accompanied by worsening of functional variables. Cigarette smoke -exposed animals receiving β -carotene dietary supplements showed an intensifi cation of heart remodeling and the harmful effects of the remodeling process, such as increase in left atrium area, myocyte cross -section area, left ventricular systolic and diastolic sizes, were heightened [134] .…”
Section: Dietary Interventions With Mixed Effects On Cigarette Smoke mentioning
confidence: 99%
“…Alguns modelos foram desenvolvidos. A bomba sanguínea espiral mostrou resolutividade por gerar escoamento e pressão adequados, sem causar danos excessivos aos elementos figurados do sangue (37) . Um modelo de coração isolado desenvolvido tipo working heart se manteve estável durante a duração dos experimentos, sem a administração de drogas cardiotônicas, e possibilitou a mensuração de todos os dados propostos de forma efetiva com o coração executando trabalho (38) .…”
Section: Cardiologiaunclassified